2005
DOI: 10.1177/1534735404274167
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Hyperglycemia as an Adjunct to Cancer Therapy

Abstract: Hyperglycemia is commonly manifested in cancer patients. Although high intakes of sugar and refined carbohydrates and elevated blood glucose are strongly associated with the risk of cancer, much less is known about their effects on survival after cancer diagnosis. There is evidence that high carbohydrate intake is associated with poorer survival after diagnosis for early breast cancer. We measured glycated hemoglobin in a group of cancer patients (some with active disease and some in remission) and found a sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 56 publications
(62 reference statements)
0
57
1
1
Order By: Relevance
“…A number of epidemiological studies have shown a direct association between breast cancer risk and the consumption of sweet foods with high glycaemic index (Lubin et al 1981, Landa et al 1994, Potischman et al 2002, Tavani et al 2006. Studies have also provided evidence that high carbohydrate intake is associated with poorer survival after diagnosis for early breast cancer (Krone & Ely 2005). Animal models of diabetes have also shown an increase in susceptibility to chemically induced mammary tumours (Shafie & Grantham 1981).…”
Section: Introductionmentioning
confidence: 98%
“…A number of epidemiological studies have shown a direct association between breast cancer risk and the consumption of sweet foods with high glycaemic index (Lubin et al 1981, Landa et al 1994, Potischman et al 2002, Tavani et al 2006. Studies have also provided evidence that high carbohydrate intake is associated with poorer survival after diagnosis for early breast cancer (Krone & Ely 2005). Animal models of diabetes have also shown an increase in susceptibility to chemically induced mammary tumours (Shafie & Grantham 1981).…”
Section: Introductionmentioning
confidence: 98%
“…Epidemiological studies corroborate the adverse role of highinsulinemic nutrition, insulin and IR in the malignant state: high intake of sugar and refined carbohydrates and elevated blood glucose were found to be strongly associated with the risk of cancer [117] and with poorer survival after diagnosis for early breast cancer [118]. Also, chronic exogenous insulin therapy significantly increases the risk of colorectal cancer among type 2 diabetes patients [119].…”
Section: Insulin and Cancermentioning
confidence: 52%
“…We believe that the paleolithic ketogenic diet by excluding "non-paleolithic" food components normalizes the pathological permeability of the intestines as also seen in a published case of Crohn's disease [22], and likely through the normalization of intestinal permeability results in lowering inflammatory factors (as also showed in our previous case reports). In addition, ketosis, based on animal meat and fat may ensure optimal supply and bioavailability of vitamins, including vitamin C [33] the high blood level of which is important for the proper functioning of the immune system and also convey antitumor effects [34].…”
Section: Discussionmentioning
confidence: 99%